The essence of ESSA: More control at the district level?. (October 2019) - Edgerton, Adam Kirk
Using a national database of state education policies related to the Every Student Succeeds Act (ESSA), as well as data from surveys, interviews, and site visits, Adam Edgerton describes how ESSA has shifted relationships among state education agencies (SEAs) and school districts. Some states have not changed their policies much despite the flexibility afforded under the law, although some states have adjusted what measures are included in their accountability systems. States also expressed concern about how to meet requirements for English language learners and students with disabilities. Overall, SEAs are designing more targeted interventions for underperforming districts, and they are focusing on providing supports rather than punishments. But in this era of increased flexibility, it is possible for states to move from one extreme — punitive test-based accountability — to another — laissez-faire leadership .